Phosphorylated and dephosphorylated linker histone H1 reside in distinct chromatin domains in Tetrahymena macronuclei. - Lu, M J (1995)
Phosphorylated and dephosphorylated isoforms of Tetrahymena macronuclear H1 were separated from each other by cation-exchange high performance liquid chromatography and used to generate a pairwise set of antisera that discriminate the phosphorylation state of this linker histone. Affinity-purified antibodies from each sera recognize appropriate H1 isoforms and stain macronuclei under appropriate physiological conditions. Immunogold localizations demonstrate that phosphorylated and dephosphorylated H1 localize nonrandomly in distinct subdomains of macronuclear chromatin. Dephosphorylated H1 is strongly enriched in the electron-dense chromatin bodies that punctuate macronuclear chromatin. In contrast, phosphorylated H1 isoforms, as well as an evolutionarily conserved H2A.F/Z-like variant (hv1) believed to function in the establishment of transcriptionally competent chromatin, are modestly enriched at the periphery of chromatin bodies and in the surrounding euchromatin. Using antibodies against TATA-binding protein, we show that transcriptionally active chromatin lies outside of the chromatin bodies in an area relatively devoid of H1. Antibodies against general core histones are more or less evenly distributed across these domains. Together, these data are consistent with a model in which phosphorylation of H1, perhaps in association with hv1, loosens the binding of H1 in chromatin leading to chromatin decondensation as part of a first-step mechanism in gene activation. In contrast, our data support the view that dephosphorylation of this linker histone facilitates or stabilizes condensed, transcriptionally silent chromatin.